Implementing an inpatient integrative medicine consult service for children with pain: A qualitative analysis - Isabel Roth; Rebecca Wells; Linda Highfield; Paula Cuccaro; Sanghamitra Misra; Joan Engebretson (Elsevier, 2021)
Objectives: Complementary and integrative medicine (CIM) therapies show clinical benefits with minimal side effects, yet challenges to effective integration in hospital settings remain. The current study aimed to better understand the process of integration of CIM therapies at a large urban pediatric hospital from the perspectives of providers, parents, and administrators. Design: The study employed an applied medical ethnography. Setting: The ethnography was conducted before, during, and after an Integrative Medicine Pain Consult Service (IM Pilot) was implemented at a large urban pediatric hospital during the spring of 2017. Main outcome measures: Fieldwork interviews, participant observations, and document review captured aspects of the integration of CIM over a 6-month study period. Ethnographic analysis included thematic content analysis. Participants included providers (n = 10), administrators (n = 5), and parents of patients (n = 11). Results: Emergent themes from analysis of the interviews and field notes were organized according to the socio-ecological model. Themes included facilitating factors for CIM pain management at the intrapersonal and community levels (Alignment with Parental Perceptions of Child Needs and Provider Desire to Offer Care, Alignment of CIM with Spiritual Beliefs and Community Norms) and barriers at the interpersonal, organizational, and political levels (Inter-professional Challenges, Lack of Logistics in Place for Referrals and Triaging Patients with Pain, Lack of Remuneration/Insurance Reimbursement for Care). Conclusions: To address barriers, future efforts to implement integrative pain management programs in pediatric hospital settings may consider testing implementation strategies, including engaging program champions and family advocates, providing education on CIM professions and therapies to hospital staff, and billing for provider time rather than individual CIM therapies.